1999
DOI: 10.1177/104990919901600110
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for enrolling dementia patients in hospice: A replication

Abstract: Because survival time varies greatly in dementia, it is difficult for dementia patients to meet a key criterion for the Medicare Hospice Benefit, a six-month survival time. In a previous study, the authors examined guidelines for admitting dementia patients to hospice; the National Hospice Organization (NHO) guidelines were found to work well in identifying appropriate candidates for hospice among dementia patients. This was especially true for those patients whose deficits had progressed in an ordinal fashion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…Contextual factors such as the use of tube feeding and less aggressive care plans (Hanrahan et al, 1999;Lapane et al, 2001) plus the inability of some scoring systems to discriminate between underlying morbidities and different disease trajectories, gender differences, and disabilities mean that existing tools and guidelines need further validation and refinement (Gambassi et al, 1999;Mitchell et al, 2004aMitchell et al, , 2004bMagaziner et al, 2005). A small descriptive study argued that the use of hospice guidelines for people with dementia were useful for identifying survival time of less than six months (Hanrahan et al, 1999), but a study that reviewed the notes of 165 people with dementia admitted to a community-based hospice found that only 64% of people who met criteria for hospice care died within six months of admission. It concluded that advanced age, anorexia and level of function were more useful prognostic indicators than existing guidelines (Schonwetter et al, 2003).…”
Section: Predicting the Approach Of Death For People With Dementiamentioning
confidence: 99%
“…Contextual factors such as the use of tube feeding and less aggressive care plans (Hanrahan et al, 1999;Lapane et al, 2001) plus the inability of some scoring systems to discriminate between underlying morbidities and different disease trajectories, gender differences, and disabilities mean that existing tools and guidelines need further validation and refinement (Gambassi et al, 1999;Mitchell et al, 2004aMitchell et al, , 2004bMagaziner et al, 2005). A small descriptive study argued that the use of hospice guidelines for people with dementia were useful for identifying survival time of less than six months (Hanrahan et al, 1999), but a study that reviewed the notes of 165 people with dementia admitted to a community-based hospice found that only 64% of people who met criteria for hospice care died within six months of admission. It concluded that advanced age, anorexia and level of function were more useful prognostic indicators than existing guidelines (Schonwetter et al, 2003).…”
Section: Predicting the Approach Of Death For People With Dementiamentioning
confidence: 99%
“…In a similar study by Hanrahan and colleagues, 10 45 patients were enrolled in hospice using the FAST 7 system. These investigators examined the efficacy of FAST in identifying patients with dementia who were appropriate for hospice.…”
Section: Prognostication In Dementiamentioning
confidence: 99%
“…The patient with AD is considered appropriate for hospice care at level 7 of the FAST, when the patient has lost the ability to perform any activities of daily living without assistance, has limited speech, and requires assistance with ambulation (Table 1). 47,48 The patient with AD must be below 50% on the KPS to meet hospice criteria, meaning the patient is unable to care for self and requires the equivalent of institutional or hospital care and that the disease may be progressing rapidly (Table 2). 46 Critics of the FAST argue that its use may prevent the admission of some patients with AD to hospice, because the FAST is an ordinal scale, and some patients with AD do not decline in an ordinal fashion.…”
Section: Tools For Determining Hospice Eligibility For Patients With Admentioning
confidence: 99%